Terahertz spectroscopy - Chen, Lili (Nanyang Technological University, 2020)
Terahertz wave has drawn many attentions in the industry as its non-ionising properties provide a lot of advantages in biomedical field and security screening. Therefore, it is worthwhile to investigate methods for generating intense THz signals under laboratory conditions. In our experiment, THz waves were generated through optical rectification by utilizing both zinc telluride and lithium niobate exposed to air at room temperature. It was found that optical rectification of femtosecond laser pulses in lithium niobate crystal through tilted-pulse-front scheme is effective in generating THz signals. Electro-optical sampling method was employed in this experiment for the detection of THz signals. The intensity of zinc telluride - generated THz is only 0.017V, while the intensity of lithium niobate crystal - generated THz is 14 times more powerful at 0.24V. In addition, spectroscopy for different types of silicon in air at the room temperature was carried out within 1 THz spectral width for THz signals generated with lithium niobate. The average absorption coefficient for silicon within 1 THz spectral width was determined to be 0.3 〖cm〗^(-1). Limitations associated with this experiment were also discussed, with the main component being the lack of cryogenic cooling to reduce the THz absorption and attenuation by the water vapor. Last but not the least, recommendations for the future research in order to improve the THz signal conversion efficiency were given. The most important recommendation is to implement the cryogenic cooling process during the generation of intense THz signal by optical rectification of femtosecond laser pulses in lithium niobate through tilted-pulse-front scheme. The cryogenic cooling plays an important role in affecting the conversion efficiency as cryogenic process reduces the absorption and attenuation of THz signals by water vapor present in the atmosphere.